Aceclofenac cocrystal nanoliposomes for rheumatoid arthritis with better dermatokinetic attributes: a preclinical study. (March 2017) - Sharma, Gajanand; Saini, Mandeep Kaur; Thakur, Kanika; Kapil, Namarta; Garg, Neeraj Kumar; Raza, Kaisar; Goni, Vijay G; Pareek, Anil; Katare, Om Prakash
Aim: The aim of present research was to complex aceclofenac with lysine (LYS) and the developed aceclofenac–LYS cocrystal was encapsulated in lipid bilayers of liposomes by employing dual carrier approach for the treatment of pain-related disorders in rheumatoid arthritis (RA).Materials & methods: The developed carriers were characterized for particle size, drug release, ex vivo and in vivo studies, dermatokinetic modeling, complete freund's adjuvant (CFA)-induced RA rat model, radiant heat tail-flick method, formalin-induced paw-licking model, paw edema model and xylene-induced ear edema model in mice.Results: The developed nanoliposomes offered nanometric size, controlled drug release and enhanced drug permeation. Further, hydrogel incorporated nanoproduct was found to be rheologically acceptable and substantially compatible with rodent skin.Conclusion: The studies indicated the superiority of LYS-conjugated liposome-entrapped nanocarriers for improved management of conditions like RA over the marketed product.